Performing Hybrid Identities, Corporeal Style. An Exploration of Three Feminist Latin American Performance Artists - Bradley, Mónica (2017)
The following article analyzes the work of three Latin American performance artists: Jesusa Rodríguez, Carmelita Tropicana, and Teresa Hernández. These three artists use their work to resist colonial, capitalist, and patriarchal oppression and bring issues of racism, borderlands, queer sexualities, gender, and neocolonialism into public discourse. Through their stirring performances, they question and push the limits of their own identities and fight against these injustices and stereotypes, often in a satirical way. El siguiente artículo analiza el trabajo de tres artistas latinoamericanas: Jesusa Rodríguez, Carmelita Tropicana y Teresa Hernández. Estas tres artistas usan su trabajo como resistencia colonial, capitalista y de opresión patriarcal, resaltando situaciones de racismo, zonas fronterizas, sexualidades queer, género y neocolonialismo en el discurso público. Por medio de sus actuaciones estimulantes, ellas cuestionan y llevan más allá los límites de sus identidades luchando en contra de estas injusticias y estereotipos, a veces de una manera satírica.